ERROR ANALYSIS MADE BY THE FIFTH SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF CATHOLIC UNIVERSITY OF SAINT THOMAS IN THEIR ENGLISH COMPOSITIONS - ANNA STASYA PRIMA SARI; Anggiat Sahat Martua Sinaga (Jurnal Suluh Pendidikan, 2020)
This research was primarily conducted to find out the total amount of grammatical errors and to analyze kinds of morphological and syntactical errors made by the fifth semester students of English Language Education Study Program of Catholic University of Saint Thomas in the Academic Year of 2018/2019 in their English compositions. There are 22 students as the research subject of the study. The writers collected the data by asking the students to write down an English composition entitled My Unforgettable Experience. The grammatical errors made by the students were analyzed based on linguistic category taxonomy (morphological and syntactical errors) proposed by Dulay et al (1982). Based on the data analysis, it was found that there are 400 grammatical errors altogether (277 morphological errors and 123 syntactical errors) made by the research subject in their English compositions. In morphological errors, the students dominantly made errors in past tense, namely 247 errors (89.2%). Next, the students made 14 errors in definite article (5.0%), 10 errors in third singular verb (3.6%), 2 errors in comparative adjective/adverb (0.7%), 2 errors in regular/irregular verbs (0.7%), 1 error in possessive case (0.4%), and 1 error in past participle (0.4%). In syntactical errors, the students dominantly made errors in transformation, namely 42 errors (34.15%). Next, the students made 30 errors in verb construction (24.39%), 25 errors in word order (20.33%), 24 errors in verb phrase (19.51%), and 2 errors in noun phrase (1.62%). It is advisable that the students had better master English grammar very well and need to equip themselves with at least a number of fundamental abilities such as how to use punctuations and construct simple sentences in the English language correctly, and the English teachers/lecturers had better explain English grammar and teach how to construct simple sentences in the English language correctly. Keywords: Error analysis, grammatical errors, morphological errors, syntactical errors, English compositions